Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.33073/pjm-2022-021
|View full text |Cite
|
Sign up to set email alerts
|

The Component and Functional Pathways of Gut Microbiota Are Altered in Populations with Poor Sleep Quality – A Preliminary Report

Abstract: With the development of genome sequencing, many researchers have investigated the mechanism by which the intestinal microbiota influences sleep across the brain-gut axis. However, the relationship between gut microbiota and sleep disorder remains unclear. Thus, we studied the difference in gut microbiota composition between poor sleep quality- and normal populations, which helps set the ground for future research. The recruited college students provided baseline information and stool samples and completed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…38 Some studies have reported that Elusimicrobia was involved in sleep quality and depression. 39,40 Our study indicated that the abundance of Elusimicrobia might be positively related to the severity of UC.…”
Section: Discussionmentioning
confidence: 66%
“…38 Some studies have reported that Elusimicrobia was involved in sleep quality and depression. 39,40 Our study indicated that the abundance of Elusimicrobia might be positively related to the severity of UC.…”
Section: Discussionmentioning
confidence: 66%
“…In addition, the prominence of butanoate metabolism toward gut microbiome involvement. Notably, previous research has indicated functional impairment in the butanoate metabolism component of the gut microbiome in individuals with poor sleep quality group compared to healthy subjects [ 58 ]. Future integration of the gut microbiome datasets could potentially unveil metabolite alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the pathophysiological mechanisms of sleep disturbance, the role of the gut microbiota has gradually attracted increasing attention. Zhang et al found that Tenericutes, Elusimicrobia, butanoate metabolism, and propanoate metabolism were the main differences between groups with poor and normal sleep quality [39]. Beyond the difference between healthy controls and insomnia patients, significant differences in taxa such as Lachnospira, Faecalibacterium, and Blautia were observed between chronic and acute insomnia patients [40].…”
Section: Introductionmentioning
confidence: 99%